Shelter Differences on Growth and Survival of Red Claw Crayfish (Cherax quadricarinatus) in Experimental Tanks - Raharjo, Siggit Dwi Raharjo; Saraswati, Erika; Yuniartik, Mega (Journal of Aquaculture and Fish Health, 2024)
Red claw crayfish (C. quadricarinatus) culture has a serious problem, which is the low survival rate caused by cannibalism. High levels of cannibalism begin to appear since the juvenile stadia, and when the lobster is moulting. Shelter is necessary during the cultivation process to reduce the level of lobster cannibalism. The purpose of this research is to study and analyze the differences in shelter on the growth and survival rate of freshwater lobster. The method used in the study was experimental with a completely randomized design (CRD). Consists of 5 treatments, including treatment without shelter (K), PVC pipe (A), roster (B), plastic hose (C), and hydrilla (D). Data were analyzed using analysis of variance in the form of one-way ANOVA (Analysis of Variance). The results of this study showed that shelter differences had a significant effect on absolute weight growth (Sig. 0.002), growth rate (Sig. 0.014), biomass weight (Sig. 0.001), survival rate (Sig. 0.001), but the difference in shelter has no significant effect on absolute length growth Sig. 0.858. The results of water quality observations found that shelter differences do not significantly affect the water quality of crayfish (C. quadricarinatus). The highest absolute weight growth was in the paralon pipe shelter with a value of 0.93 g, the highest length growth was in the roster shelter at 1.22 cm, the highest growth rate was in the PVC pipe shelter at 0.027 g/day, the highest biomass weight was in the PVC pipe shelter 32.64 g, the highest survival rate was in the PVC pipe shelter 92.6%.